ANALISA KERUSAKAN JARINGAN IRIGASI DAERAH IRIGASI MERJAN KABUPATEN PANGANDARAN - SUMBONO, IGO (Prosiding Seminar Nasional Sains dan Teknologi, 2025)
The Merjan Irrigation Area, under the jurisdiction of the Ciwulan-Cilaki Water Resources Management Unit (UPTD SDA) and within the working area of ​​the Cimedang-Ciputrapinggan Water Resources Management Unit (SUP WS) in Pangandaran Regency, irrigates 1,631 hectares of rice fields. Damage to the irrigation canals and structures has resulted in suboptimal water supply for rice fields, negatively impacting farmers. This study conducted a survey to determine the physical condition of the canal structures and to calculate water discharge, efficiency, water loss, and irrigation effectiveness in the Merjan Irrigation Area. The results of these calculations provide insights into the performance of the irrigation area. From the results of the study, the condition of the main building was obtained, the results were 50.00% (sufficient), the carrier channel was 34.30% (damaged), the distribution/tapping building was 25.00% (damaged), the discharge channel was 54.26% (sufficient), the building along the discharge channel was 39.02% (damaged) while from the results of the calculation of water discharge in the Merjan irrigation channel was 0.2753%, for the efficiency of the irrigation channel was 64.48% and for the effectiveness value of the irrigation network was 47.00% and water loss was 30.50%. The OP aspect of the irrigation network is in category 1 (less) From these results, the Merjan irrigation network requires rehabilitation.